THE EFFECT OF PROJECT BASED LEARNING TO THE STUDENTS’ SPEAKING ABILITY - Mafruudloh, Naajihah; Fitriati, Rahima (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
Project based learning (PBL) is an appropriate and applicable learning method in all levels of education. In this method, the lecturer acts as a facilitator or the one who takes a main role in teaching and learning process. The aim of PBL is to solve problems and develop students’ critical thinking. It also encouraged the students’ way of thinking in doing or creating something.  This method was implemented in English for Management class at. It was expected to make the students to be more creative facilitated by a discussion, sharing, and collaboration work. The aim of this study was to describe the implementation of PBL in non-English department class (Management department class) and to know the effect of PBL in students’ speaking ability. There were 25 students selected as the sample. The methodology used pre-experimental design. Data were collected by observation to answer the first research question and test to answer the second research question. The acquired quantitative data were analysed statistically by paired sample T-test. The research found a significant effect of PBL to the students’ speaking ability. It was also an effective methodology in teaching speaking because it made the students to be more active and innovative in doing the task and joining the class.  Thus, it is strongly recommended to apply this teaching method in speaking class as an alternative way to improve students’ speaking competency.